2015
DOI: 10.1007/s13204-015-0401-2
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of silver nanoparticles from Cavendish banana peel extract and its antibacterial and free radical scavenging assay: a novel biological approach

Abstract: Biosynthesis of metallic silver nanoparticles has now become an alternative to physical and chemical approaches. In the present study, silver nanoparticles (AgNPs) were synthesized from Cavendish banana peel extract (CBPE) and characterized by UV-visible spectroscopy, X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, Atomic force microscopy (AFM), Field emission scanning electronic microscope (FESEM), Dynamic light scattering (DLS) and zeta potential (ZP). The AgNPs formation was confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
83
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 34 publications
12
83
0
1
Order By: Relevance
“…ions to Ag-NPs, while the starch acted as a stabilizing agent for the Ag-NPs (Patil et al 2012;Vigneshwaran et al 2006). Similar observations in green synthesis of Ag-NPs using plant extracts have been reported by many researchers (Donda et al 2013;Kokila et al 2015;Prakash et al 2013;Shankar et al 2014a;Shinde et al 2014). …”
Section: Synthesis Of Silver Nanoparticlessupporting
confidence: 86%
“…ions to Ag-NPs, while the starch acted as a stabilizing agent for the Ag-NPs (Patil et al 2012;Vigneshwaran et al 2006). Similar observations in green synthesis of Ag-NPs using plant extracts have been reported by many researchers (Donda et al 2013;Kokila et al 2015;Prakash et al 2013;Shankar et al 2014a;Shinde et al 2014). …”
Section: Synthesis Of Silver Nanoparticlessupporting
confidence: 86%
“…Our previous report demonstrated that silver nanoparticles can successfully be synthesized in a facile and cost-effective way using leaf extracts of Piper nigrum (Augustine et al 2014e). Biosynthesized silver nanoparticles were reported for their excellent antibacterial activity against wide range of microorganisms (Gnanadesigan et al 2012;Kathiraven et al 2014;Netala et al 2014;Sinha et al 2014;Kumar et al 2015;Kokila et al 2015;Roy et al 2014). Antifungal activity of biosynthesized silver nanoparticles is also well studied (Kumar et al 2013;Medda et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The difference between chemically produced and biologically synthesis Ag nanoparticles has also been reported by Kokila et al, for banana peel extract. 36 The present study revealed Escherichia coli (gramnegative) displayed a larger inhibition zone compared with Staphylococcus Epidermis (gram-positive). The most likely cause for this difference is due to the variation in cell wall composition of the two-gram types.…”
Section: Discussionmentioning
confidence: 48%